Assessment of the role of cannabinoid receptor 2 in innate immune cell trafficking during acute inflammation - Taylor, L (2016)
Activation of the cannabinoid receptor CB2 has been shown to induce directed leukocyte migration and inhibit leukocyte chemotaxis towards CC chemokines. However, the role that CB2 plays in regulating macrophage chemotaxis remains understudied. Using a real-time chemotaxis assay and a panel of chemically diverse CB2 agonists, I set out to examine whether CB2 modulates primary macrophage chemotaxis. Of 14 agonists tested, only a subset acted as bona fide macrophage chemoattractants. Surprisingly, despite being pertussis toxin-sensitive, neither pharmacological inhibition nor genetic ablation of CB2 had any effect on CB2 agonist-induced macrophage chemotaxis. Furthermore, the activation of CB2 had no effect on CCL2 or CCL5- induced macrophage chemotaxis. Therefore, the activation of CB2 does not inhibit CC chemokine-induced macrophage migration and a non-CB1/CB2, Gi/o-coupled GPCR must transduce CB2 agonist-induced macrophage chemotaxis. To identify the GPCR responsible, I examined primary murine macrophage GPCR expression and found that they express 124 non-sensory GPCRs. Functional screening of candidate receptors demonstrated that the putative cannabinoid receptors GPR18 and GPR55 and the lipid binding GPCRs LPAR1&5, CYSLTR1&2 and GPER1, were not responsible for CB2 agonist-induced macrophage chemotaxis. Alongside, a ligand-directed virtual screen, combined with functional testing, uncovered a novel chemotaxis positive chemical scaffold. Importantly, compounds in this series containing a photoaffinity label retained activity and will aid in the identification of the target(s) responsible for CB2 agonist-induced macrophage chemotaxis in future photocrosslinking experiments. Finally, I assessed whether CB2 controls innate immune cell recruitment in vivo using the zymosan-induced dorsal air pouch inflammation model and animals genetically deleted for CB2. I found that CB2-/- mice had increased air pouch neutrophil and monocyte numbers, as well as pro-inflammatory mediators, during the acute inflammatory phase. Interestingly, mixed bone marrow chimera experiments demonstrated that lack of CB2 specifically in the myeloid population is responsible for increased neutrophil trafficking. Therefore these data demonstrate that CB2 acts to regulate neutrophil recruitment during the acute inflammatory response.